91 PREDICTORS OF PREMATURE CORONARY ARTERY DISEASE AND DIFFERENTIAL LONG-TERM OUTCOMES IN PATIENTS STRATIFIED BY PRESENCE OF CORONARY ARTERY DISEASE AND CARDIAC REVASCULARIZATION. (1st March 2005) - Nathan, S.; Amin, A. P.; Attanasio, S.; Mehta, V.; Kelly, R. F.
Abstract : Introduction: While premature coronary artery disease (PCAD) is associated with an adverse prognosis, limited data are available in the public health system population. Little is certain with respect to cardiac risk factors (CRFs), short-term mortality and long-term outcomes with or without coronary revascularization. Hence we explored the prevalence of CRFs and predictors of mortality in patients with PCAD and characterized the effect of revascularization on survival in a public health system patient cohort. Methods: Data from 416 consecutive patients ≤ 40 yrs of age undergoing coronary angiography at Cook County Hospital (1993-2001) were compiled prospectively and analyzed as an open, retrospective cohort. The primary outcome measure was mortality analyzed via Kaplan-Meier analysis. Risk of CAD (defined as ≥ 50% stenosis in ≥ 1 coronary artery) by cardiac risk factors were estimated using logistic regression. Angiographic data were adjudicated by blinded film review. Results: 1, 444 pt-yrs of follow-up were attained. Of 416 patients, 33% (136) had premature CAD, of which 96% (131) had severe CAD (≥ 70% stenosis). The prevalence of risk factors as follows was higher than previously reported: DM 18.2%, smoking 50.9%, dyslipidemia 14.3%, family history 22.4% and hypertension 52.5%. Total mortality at 3.47 years mean follow-up was 5.8% and was higher with severe CAD (9.2% if CAD vs. 4.2% if no CAD, p = 0.044). Diabetes mellitus (O.R. 3.71 [1.13-12.2], p = 0.031) and systolic dysfunction (O.R. 3.13 [1.0-9.81], p = 0.05) each independently predicted mortality. Of the 136 patients with PCAD, 82 patients (60.3%) underwent revascularization: 48 (35.3%) PTCA, 38 (27.9%) stenting, 17 (12.5%) both PTCA and stenting, and 13 (9.6%) CABG. Of the total 12 (9.9%) deaths, there was a trend towards lower mortality in revascularized patients (8.5% vs. non-revascularized patients 12.5%, p = 0.17). Kaplan-Meier survival curves by revascularization status were clearly divergent (p value NS). Conclusions: Diabetes, smoking, dyslipidemia and older age were predictive of PCAD. Diabetes and left ventricular dysfunction were independent predictors of overall mortality even after adjusting for the effect of PCAD. There was a trend towards improved survival in PCAD patients undergoing revascularization.